Changes in stress pathways as a possible mechanism of aerobic exercise training on brain health: a scoping review of existing studies - Molina-Hidalgo, Cristina; Stillman, Chelsea M.; Collins, Audrey M.; Velazquez-Diaz, Daniel; Ripperger, Hayley S.; Drake, Jermon A.; Gianaros, Peter J.; Marsland, Anna L.; Erickson, Kirk I. (Frontiers in Physiology, 2023)
Physical activity (PA) in the form of aerobic exercise (AE) preserves and improves neurocognitive function across the lifespan. However, a mechanistic understanding of the pathways by which AE impacts brain health is still lacking, particularly with respect to stress-related pathways. One mechanistic hypothesis is that AE improves neurocognitive health in part by modifying circulating levels of stress-related hormones and signaling factors associated with the hypothalamic-pituitaryadrenal (HPA) axis and autonomic nervous system (ANS), as commonly measured by the biomarkers cortisol (CORT) and salivary α-amylase (sAA). Thus, this hypothesis predicts that changes in stress biomarkers, such as CORT and sAA, are possible explanatory pathways mediating the positive effects of AE on neurocognitive health. In the present review article, we provide a summary of available studies examining the possibility that exercise-induced changes to stress biomarkers could partly account for exercise-related improvements in neurocognitive health. Our review indicates that despite the intuitive appeal of this hypothesis, there is insufficient evidence available to conclude that chronic and habitual AE affects neurocognitive health by altering stress biomarker pathways. The crosssectional nature of the majority of reviewed studies highlights the need for well-controlled studies to adequately test this hypothesis.as a possible mechanism of aerobic exercise training on brain health: A scoping review of existing studies 2 Stress Biomarkers: CORT and SAA The concept of stress has been used across disciplines with different methodological approaches. A global definition of this concept comes from Cohen et al. (2016), who defined stress as "a set of constructs representing stages in a process by which environmental demands that tax or exceed the adaptive capacity of an organism occasion psychological, behavioral, and biological responses that may place persons at risk for disease" (Cohen, Gianaros, & Manuck, 2016). According to the Changes in stress biomarkers as a mechanism of aerobic exercise training on brain health: A scoping review of existing studies